2020
DOI: 10.1111/gcb.15139
|View full text |Cite
|
Sign up to set email alerts
|

Food web transfer of plastics to an apex riverine predator

Abstract: As a rapidly accelerating expression of global change, plastics now occur extensively in freshwater ecosystems, yet there is barely any evidence of their transfer through food webs. Following previous observations that plastics occur widely in their prey, we used a field study of free‐living Eurasian dippers (Cinclus cinclus), to test the hypotheses that (1) plastics are transferred from prey to predators in rivers, (2) plastics contained in prey are transferred by adults to altricial offspring during provisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(38 citation statements)
references
References 85 publications
0
33
1
Order By: Relevance
“…Some ingested plastic that we documented in our T. s. elegans field sample may also have been attributable to trophic transfer (i.e., turtles eating prey that had itself ingested or become entangled in plastic). Trophic transfer was recently reported in a riverine bird 9 and potentially in some freshwater fishes 75 . For certain sea turtle species, eating jellyfish or seagrass with ingested/entangled plastic could facilitate trophic transfer 35 , 76 , as could eating benthic bivalve mollusks in marine and freshwater systems.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some ingested plastic that we documented in our T. s. elegans field sample may also have been attributable to trophic transfer (i.e., turtles eating prey that had itself ingested or become entangled in plastic). Trophic transfer was recently reported in a riverine bird 9 and potentially in some freshwater fishes 75 . For certain sea turtle species, eating jellyfish or seagrass with ingested/entangled plastic could facilitate trophic transfer 35 , 76 , as could eating benthic bivalve mollusks in marine and freshwater systems.…”
Section: Discussionmentioning
confidence: 94%
“…Given the well-documented negative individual-level impacts of plastic pollution on marine organisms, freshwater organisms are likely to be similarly affected—assuming that similar amounts of plastic exist in marine and freshwater habitats. However, both plastic volume and impacts to wildlife in freshwater systems remain comparatively understudied 6 9 .…”
Section: Introductionmentioning
confidence: 99%
“…While studies of the transfer of microplastics across trophic levels in terrestrial system are scarce, microplastics have been found in the digestive tracts of carnivorous terrestrial birds, which suggests that they can be transferred up the food chain (Carlin et al, 2020; D'Souza et al, 2020; Zhao et al, 2016). Bioaccumulation of microplastics in terrestrial organisms was first reported by Huerta Lwanga, Gertsen, et al (2017) and Huerta Lwanga, Mendoza, et al (2017).…”
Section: The Need To Move Toward Ecological Studiesmentioning
confidence: 99%
“…Terrestrial and aquatic food webs are generally intertwined by organisms, which are mobile and occupy large spatial area (e.g., birds and winged insects), and can seamlessly transit ecotones (Knight et al, 2005). A recent study (D’Souza et al, 2020) showed that microplastics can be transferred from aquatic to terrestrial ecosystems, when aquatic insects (Ephemeroptera and Trichoptera; 26 ± 3 particles/g) are consumed by passerines ( Cinclus cinclus ; regurgitated pellets 16 ± 3 particles/g, feces 8 ± 2 particles/g).…”
Section: The Need To Move Toward Ecological Studiesmentioning
confidence: 99%
“…Up to now, it has been estimated that around 260 species, including marine mammals, birds and sea turtles, are threatened by PD, via entanglement and/or ingestion (Caron et al, 2018;Isangedighi et al, 2018). Moreover, breaking down into smaller fragments and filaments (Rocha- Santos and Duarte, 2015;Peng et al, 2017), plastics enter the marine food webs through ingestion by a large number of fish and shellfish species (Barboza et al, 2018), progressively accumulating across the food chain up to the top predators, including humans (Rochman et al, 2015;Nelms et al, 2018;D'Souza et al, 2020).…”
Section: Introductionmentioning
confidence: 99%